P186 The association between social deprivation and disease activity in rheumatoid arthritis: a systematic literature review. (23rd April 2022) - Dey, Mrinalini; Busby, Amanda; Elwell, Helen; Lempp, Heidi; Pratt, Arthur; Isaacs, John D; Nikiphorou, Elena
Abstract: Background/Aims: It is clear that physical and mental illnesses are driven by ethnicity, social, environmental and economic determinants. Novel theoretical frameworks in RA focus on links between biological and non-biological (social) factors and adverse interactions within specific social contexts. This review aimed to summarise the existing evidence on associations between social deprivation and RA disease activity, and implications for research going forward. Methods: Articles studying the association between socioeconomic status (SES) and RA disease activity were included, published from 1946 until March 2021. Initial scoping reviews were performed to optimise the search strategy, especially with regards to the exposure and outcome variables. The focus of the review was on the effect of "socioeconomic status" or similar database indexing terms, on disease activity (and similar indexing terms). The databases Medline, Embase, International Network of Agencies for Health Technology Assessment, PsychInfo and Cochrane Databases were searched. The research question, using the 'Patients, Intervention, Comparator or Control, Outcome, Type of study' format was as follows: Is there an association between social deprivation and disease activity in people with rheumatoid arthritis? The search was restricted to English-language articles only. Articles deemed eligible were: observational studies, qualitative studies and randomised controlled trials. Titles and abstracts were screened to assess eligibility. The full articles which met inclusion criteria were then examined in detail by one author. For validation, 10% of articles were screened at the abstract and full paper stage by a second author. Disagreements were resolved through discussion and input from a third reviewer. Information was extracted on definition/measure of SES, ethnicity, education, employment comorbidities, disease activity and the presence/absence of association between social deprivation and disease activity. Results: In the initial search, 1750 articles and 797 conference abstracts were identified. After deduplication, this was reduced to 1299 full papers. After screening title and abstract, 1268 papers were excluded, with 31 proceeding to full-text screening. Ultimately, 30 articles (all observational studies) were included in the review. There was marked variation in definition of SES, with ten articles using a formal scale or measure, the majority using educational attainment as a proxy. Most studies controlled for lifestyle factors including smoking and BMI, as well as comorbidities. 25 articles concluded an association between SES and RA disease activity, two articles were unclear, and three found no association. Conclusion: Our review highlights the association between low SES and worse disease outcomes in patients with RA, consistent with previous work in this area. We have demonstrated the complex multifaceted relationships giving rise to this association. There is a need for increased application of mixed-methods methodology and consideration of syndemic frameworks to understand bio-bio and bio-social interactions, to examine drivers of disease and poor clinical outcomes more holistically. Disclosure: M. Dey: None. A. Busby: None. H. Elwell: None. H. Lempp: None. A. Pratt: None. J.D. Isaacs: None. E. Nikiphorou: None.